Unraveling the metastasis‐preventing effect of miR‐200c in vitro and in vivo - Bianca Köhler; Emily Brieger; Tom Brandstätter; Elisa Hörterer; Ulrich Wilk; Jana Pöhmerer; Anna Jötten; Philipp Paulitschke; Chase P. Broedersz; Stefan Zahler; Joachim O. Rädler; Ernst Wagner; et al. (Molecular Oncology)
Advanced breast cancer, as well as ineffective treatments leading to surviving cancer cells, can result in the dissemination of these malignant cells from the primary tumor to distant organs. Recent research has shown that microRNA 200c (miR‐200c) can hamper certain steps of the invasion–metastasis cascade. However, it is still unclear whether miR‐200c expression alone is sufficient to prevent breast cancer cells from metastasis formation. Hence, we performed a xenograft mouse experiment with inducible miR‐200c expression in MDA‐MB 231 cells. The ex vivo analysis of metastatic sites in a multitude of organs, including lung, liver, brain, and spleen, revealed a dramatically reduced metastatic burden in mice with miR‐200c‐expressing tumors. A fundamental prerequisite for metastasis formation is the motility of cancer cells and, therefore, their migration. Consequently, we analyzed the effect of miR‐200c on collective‐ and single‐cell migration in vitro, utilizing MDA‐MB 231 and MCF7 cell systems with genetically modified miR‐200c expression. Analysis of collective‐cell migration revealed confluence‐dependent motility of cells with altered miR‐200c expression. Additionally, scratch assays showed an enhanced predisposition of miR‐200c‐negative cells to leave cell clusters. The in‐between stage of collective‐ and single‐cell migration was validated using transwell assays, which showed reduced migration of miR‐200c‐positive cells. Finally, to measure migration at the single‐cell level, a novel assay on dumbbell‐shaped micropatterns was performed, which revealed that miR‐200c critically determines confined cell motility. All of these results demonstrate that sole expression of miR‐200c impedes metastasis formation in vivo and migration in vitro and highlights miR‐200c as a metastasis suppressor in breast cancer.